Managing improving primary schools : using evidence-based management and leadership - Southworth, Geoff (Falmer Press, 1999)
A practical handbook which senior staff in primary schools can use to support their activities in evidence-based management. This book will provide guidance on the need to conduct and act upon quality reviews and evidence-based analysis.